Effect of optimizing sodium substitution formula on the storage quality and shelf life of Oncorhynchus masou caviar - Linggao Liu; An Wang; Chunming Tan; Pinglan Li; Ruiyun Wu (Food Science of Animal Products)
This study aimed to investigate the effect of using an optimized complex sodium salt substitute formulation, comprising potassium lactate (17.64%), potassium chloride (14.61%), magnesium chloride (34.36%), and sodium chloride (33.39%), on the quality of Oncorhynchus masou caviar at different storage temperatures and to compare it with the traditional sodium chloride curing method. Caviar samples were stored at 20, 27, and 34 °C, respectively, and the effect of the new formulation on the quality characteristics of the caviar was systematically evaluated through the determination of microbiological indicators, pH, water activity, total volatile basic nitrogen content and other physicochemical indicators. In addition, the shelf life of the samples at 0 and 4 °C was predicted using the accelerated shelf life test model. The results showed that using sodium salt substitute formulation could effectively inhibit microbial growth, slow down the spoilage process of the product, and significantly extend the shelf-life of caviar, which is a significant advantage over the traditional sodium chloride curing method. This study provides theoretical support and practical guidance for the improvement of caviar processing technology and salt reduction in the food industry.